Análise da variabilidade induzida pela concentração de co2 nas leituras de medidores de vazão ultrassônicos para gás de queima - Barros, Weverton Ferreira (2016)
The produced effect by the attenuating character of the carbon dioxide on the ultrasonic flowmeter performance in gas flare application was verified. For this, experiments were conducted in wind tunnel with Reynolds number at 104. The results indicates that the ultrasonic meter presented measurement failures in stages of abrupt variation of this gas and whose concentration was show higher of 5%, also being verified that an approximation of the transducers tend to reduce this failures of measurement